BIOMEDICAL WASTE MANAGEMENT IN A TERTIARY CARE HOSPITAL. A SCIENTIFIC REVIEW. - Ahmed Hasan Mohamed Alomri, Wail Abdullah Salem Alsubhi, Basmah Mohammed Hasan Aljehani, Maryam Mohammad Hassan Rajeh, Ghadah Hamed Mutlaq Alrefaei, Ibrahim Mohammed Abdullah Alabdullah, Sami Abdullah Al-Ghamdi, Alaa Hassan Alharbi, Naif Ahmed Alharbi,,; Faris Eid Alghamdi, (Chelonian Research Foundation, 2023)
The interaction of the micro- (internal) and macro- (surrounding) environments of human beings determines the status of the health of an individual or of the community at large. On a daily basis, the generation and disposal of biomedical waste have become an emerging problem world over. These are being produced during the processes of sampling, testing, diagnosis, therapy, immunization, and surgery on humans, animals, and in research experiments. Several categories of biomedical waste have been discussed, and steps involved in the management of biowaste include segregation, storage in containers, labeling, handling, transport, treatment, disposal, and waste minimization. Potential implications of biomedical wastes include transmission of diseases like Hepatitis B, C, E, dengue, and HIV through improperly contained contaminated sharps; proliferation and mutation of pathogenic microbial populations in municipal waste through dumping of untreated biomedical waste; and physical injury and health hazards. Certain other implications include degradation of the environment esthetically by careless disposals, having a negative effect on public health; increased risk of nosocomial infections; change of microbial ecology and spread of antibiotic resistance; and increased density of the vector population, resulting in the spread of diseases in public. Sensitization and public awareness are important to protect the environment and public health globally. Keywords- Biomedical waste, hospital environment, health, infection